Isolation of Yersinia spp. from bovine feces. - Fukushima, H (1983)
Yersinia spp. were sought in 618 fecal samples from cows. Four strains of Yersinia enterocolitica, serotype O:12,26 (one), O:13,7 (two), and O:18 (one); seven strains of Yersinia kristensenii, serotype O:11,24 (five) and O:12,26 (two); and one strain of Yersinia pseudotuberculosis serotype IIB, were isolated. This is the first time that Y. pseudotuberculosis has been isolated from cows in Japan, and the isolation of serotype IIB of this organism from cows seems to be the first in the world.